Francés - Francés, Francés; Francés, Francés; Francés, Francés; Francés, Francés (Ars Pharmaceutica (Internet), 1991)
When subjected to ’activating’ plasrnolytic treatrnents, several Ascornycetes exhibit an enzyrnic activity which degrades 1,4-α-D-glucans to 1,5-D-anhydrofructose, then converts this sugar to ascopyrone P (in Pezizales) or ascopyrone T (in TuberaJes). Biogenetical, rnycological and practical implications of these bioconversions are discussed.